Skin whitening among Cameroonian female university students: knowledge, attitudes, practices and motivations - Emmanuel Armand Kouotou; Jobert Richie N. Nansseu; Hugues Adegbidi; Theophane Christel Joel Zoa Mebara; Elie Claude Ndjitoyap Ndam (BMC, 2017)
Abstract Background Lack of data on skin whitening (SW) among Cameroonian female university students prompted us to undertake the present study which aimed at assessing the knowledge, attitudes, practices and motivations of female university students vis-a-vis SW. Methods This was a cross-sectional study conducted from January to April 2013 in 4 university campuses of Yaoundé, Cameroon. Any female student regularly registered in one of the study sites, who was present at the campus when the investigator visited and volunteered to participate in the study was enrolled. Results Overall, we recruited 620 female students, their ages ranging from 16 to 46 years with a mean of 21.3 ± 2.9 years. Only 87 participants (14%) found that SW was a good practice. One hundred and sixty nine respondents (27.3%) were currently practicing SW with no age difference when compared to their counterparts (p = 0.09). The desire to have a uniform body skin color was the prevailing reason motivating the practice of SW (39.1%), followed by the need to have a soft skin (29%). Assessment of levels of knowledge regarding advantages of the black skin and deleterious effects of SW showed excellent scores (≥75% of good answers) only in 6.1 and 0.5% of cases respectively, with no difference between those practicing SW or not (all p values > 0.05). Conclusion The practice of SW is common among Cameroonian female university students who should therefore be educated on the advantages of the black skin and the harmful effects of SW.